Wound Healing Activity of Ethanolic Extract of Bryophyllum calycinum Salisb - Kumar, Praveen; Tripathi, Laxmi (Asian Journal of Chemistry, 2013)
In light of the Nigerian traditional claim to use Bryophyllum calycinum Salisb in the treatment of wounds, an investigation was carried out to evaluate the wound healing activity of ethanolic extract obtained from the dried whole plant of B. calycinum. The wound healing activity was evaluated using excision, incision and dead space wound models and acute toxicity study was also performed. The study demonstrated that the ethanolic extract of B. calycinum accelerates wound healing process as compared with placebo controls. Wound contraction, increased tensile strength and increased hydroxyproline content support the above finding.